Effect of milk intake and method of weaning on calf performance and stress in an early-weaning program - Flynn, P.; Reddy, P.G.; Morrill, J.L.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
Feeding milk at 8% of birthweight and gradual weaning resulted in the most consistent increases in weekly weight gain, highest overall weight gain, and greatest increases in dry feed consumption during an 8-wk trial compared to feeding milk at 8% and abrupt weaning, at 10% and gradual weaning, or at 10% and abrupt weaning. By 8 wk, the 8% gradually-weaned calves also had higher levels of serum protein and lower levels of urea nitrogen in blood than calves in other treatment groups. Therefore, the 8% gradual-weaning program was determined to be the most appropriate for early weaning of dairy calves.
Keywords: Dairy; Milk intake; Calf performance; Stress; Weaning